ITRAQ-Based Proteomics Analysis Reveals the Effect of Neoliensinine on KCl-Induced Vascular Smooth Muscle Contraction by Inhibiting Regulatory Light Chain Phosphorylation - Yang, Guang-Ming; Yan, Ke; Wang, Peng; Zhang, Jun-Li; Pan, Zi-Hao; Pan, Yang (Frontiers in Pharmacology, 2019)
Smooth muscle (SM) contraction is one of the important physiological functions of human body, and SM abnormal contraction will induce many diseases. The phosphorylated regulatory light chains (p-RLC) play a decisive role in SM contraction, and dephosphorylation of p-RLC is an effective way to relax SM. Our previous study showed that the novel benzylisoquinoline alkaloid, neoliensinine (Neo) could relax microvascular SM contracted by KCl-hyperpolarization. In this study, mesenteric capillaries isolated from 45 mice were divided into normal tension group (Control), 124 mM KCl induced contraction model group (Model), and KCl and Neo-treatment group (Drug). The dephosphorylation levels of RLC in the three groups were measured. Compared with model group, the phosphorylation of RLC in drug group was decreased dramatically as expected, suggesting that the relaxation effect of Neo was caused by downregulating p-RLC of microvessel SM. In order to fully understand its fundamental mechanism, our research focused on the identification of target proteins in mice with KCl-induced contractile mesenteric capillary. ITRAQ (isobaric Tags for Relative and Absolute Quantification)-tagging was carried out by Nanospray-liquid chromatography-tandem mass spectrometry. The results allowed the upregulation of 164 differential abundance proteins (DAPs) among the 3,474 protein abundance disturbances identified from the Model/ Control samples. Further comparison showed that there were 16 DAPs convergences associated with vascular SM contraction between the Drug/ Model and the Drug/ Control samples. Among them, two proteins with known function, PLCβ and RhoGEF12 were selected as target proteins of the relaxation effect of Neo. The two selective target DAPs were verified by Western blot at protein level. The results suggested that changes of the two proteins were consistent with that of the iTRAQ results. Our present work reveals that Neo relaxes vascular smooth muscle via inhibition of RLC phosphorylation, and PLCβ and RhoGEF12 may be potential biomarkers for evaluating the effects mediated by Neo.